Análisis comparativo de los mecanismos de selección de jueces en los países que conforman la Alianza del Pacífico y comentarios a la normativa pertinente. - Palomino Venero, Berenice Lucia (2022)
The purpose of this research work is to analyse comparatively the processes of selection and appointment of judges in the countries that are part of the Pacific Alliance, considering the success that this political and economic alliance has achieved in the region. In this sense, a historical, contextual and normative review of the institutions involved in this process is proposed, in order to comment later on the regulations in force in Peru.